The nature and correlates of paid and unpaid work among service users of London Community Mental Health Teams. - Lloyd-Evans, B; Marwaha, S; Burns, T; Secker, J; Latimer, E; Blizard, R; Killaspy, H; Totman, J; Tanskanen, S; Johnson, S (2013)
Aims. Little is known about how the rates and characteristics of mental health service users in unpaid work, training and study compare with those in paid employment. Methods. From staff report and patient records, 1353 mental health service users of seven Community Mental Health Teams in two London boroughs were categorized as in paid work, unpaid vocational activity or no vocational activity. Types of work were described using Standard Occupational Classifications. The characteristics of each group were reported and associations with vocational status were explored. Results. Of the sample, 5.5% were in paid work and 12.7% were in unpaid vocational activity, (including 5.3% in voluntary work and 8.1% in study or training). People in paid work were engaged in a broader range of occupations than those in voluntary work and most in paid work (58.5%) worked part-time. Younger age and high educational attainment characterized both groups. Having sustained previous employment was most strongly associated with being in paid work. Conclusions. Rates of vocational activity were very low. Results did not suggest a clear clinical distinction between those in paid and unpaid activity. The motivations for and functions of unpaid work need further research.